2022
DOI: 10.3390/app121910043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Hydrostatic Pressure Processing on Starch Properties of Cassava Flour

Abstract: The aim of this study was to utilize high-pressure processing (HPP) to modify cassava flour through altering the starch components. Specifically, the effect of HPP processing variables, i.e., pressure (0.10 or untreated, 300, 400, 500, and 600 MPa), flour concentration (FC; 10, 20, and 30%), and holding time (HT; 10 and 30 min) on starch-related properties was studied. Microstructural integrity, thermal properties, and starch susceptibility to digestive enzymes were determined. A three-way ANOVA was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…An HHP-driven investigation on cassava starch 25 showed transformation from crystallinity to an amorphous state. HPP-induced gelatinization (500 to 600 MPa) with a decrease in flour concentration and increase in holding time favors an increase in rapidly digestible starch with decreased resistant starch fraction.…”
Section: Modification Of Starch By Different Processesmentioning
confidence: 99%
“…An HHP-driven investigation on cassava starch 25 showed transformation from crystallinity to an amorphous state. HPP-induced gelatinization (500 to 600 MPa) with a decrease in flour concentration and increase in holding time favors an increase in rapidly digestible starch with decreased resistant starch fraction.…”
Section: Modification Of Starch By Different Processesmentioning
confidence: 99%
“…Adopting these technologies for food pasteurization not only helps retain the original flavours, aromas, and delicate bioactive components of food due to lower heat application, but also ensures the production of safe and healthy clean-label foods, as no chemical preservatives are required. Beyond their preservation benefits, HPP, PEF, and UV-C also hold a great promise for enhancing specific quality attributes in diverse food items, such as pea and soy protein isolates [4], cassava flour [5], oat flour [6], and prickly pear cactus fruit juice [7].…”
mentioning
confidence: 99%
“…Conde et al explored the influence of high-hydrostatic-pressure (HHP) processing on the properties of starch in cassava flour [5]. The study revealed that the application of 600 MPa consistently induced a transformation from crystalline to amorphous starch structures.…”
mentioning
confidence: 99%